Genetic variants at 10p11 confer risk of Tetralogy of Fallot in Chinese of Nanjing. - Jing Xu; Yuan Lin; Linjie Si; Guangfu Jin; Juncheng Dai; Cheng Wang; Jiaping Chen; Min Da; Yuanli Hu; Chenlong Yi; Zhibin Hu; Hongbing Shen; et al. (PLoS ONE)
A recent genome-wide association study (GWAS) has identified a new subset of susceptibility loci of Tetralogy of Fallot (TOF), one form of cyanotic congenital heart disease (CHD), on chromosomes 10p11, 10p14, 12q24, 13q31, 15q13 and 16q12 in Europeans. In the current study, we conducted a case-control study in a Chinese population including 1,010 CHD cases [atrial septal defect (ASD), ventricular septal defect (VSD) and TOF] and 1,962 controls to evaluate the associations of these loci with risk of CHD. We found that rs2228638 in NRP1 on 10p11 was significantly increased the risk of TOF (OR = 1.52, 95% CI = 1.13-2.04, P = 0.006), but not in other subgroups including ASD and VSD. In addition, no significant associations were observed between the other loci and the risk of ASD, VSD or TOF. Our results suggested that the genetic variants on 10p11 may serve as candidate markers for TOF susceptibility in Chinese population.